Preservation of Salapan Dance in Rabi Jonggor Kenagarian, Gunung Tuleh District, West Pasaman Regency - Dona Indriani; Herlinda Mansyur (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to reveal and describe the efforts to preserve Salapan Dance in Kenagarian Rabi Jonggor Gunung Tuleh District, West Pasaman Regency. The type of research is qualitative with descriptive methods. The research instrument is the researcher himself, with the help of supporting tools such as stationery, a camera, and a flash drive. Data collection techniques were carried out by means of literature study, observation, interviews, and documentation. The steps of data analysis are data collection, data reduction, and data conclusion. The results showed that the Salapan Dance preservation efforts collaborated with Sangar Tari Paraman Saiyo and the people of Kenagarian Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency. Salapan dance training in the studio has increased the number of performers, and the dance coaching is going well. So now Salapan Dance has a successor generation to maintain the existence of Salapan Dance. This Salapan dance has a positive impact and can be accepted by the community because many of the dance performers are community members. The impact learned in this Salapan Dance is that those who previously did not understand dance can now dance a dance that is taught, namely Salapan Dance.